Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

By polynomial formula $$(\sum_{i\in m} x_i)^n=\sum_{\substack{j_i \in \mathbb{Z}^+ \\ \sum j_i=n}}\left(\begin{array}{c} n\\ j_{0},\ldots , j_{m-1} \end{array}\right)\prod_{i \in m} x_i^{j_i}$$ where $n \in \mathbb{N}$

But what about $n \not \in \mathbb{N}$? For example $(a+b+c)^{\sqrt{3}}$? These cases probably do not have polynomial formula, but do these cases have a infinite sum like a polynomial formula?

share|cite|improve this question
up vote 1 down vote accepted

When $n$ is not an integer, multivariate Taylor series expansion is to be applied. Let's expand $(a+b+c)^{\alpha}$ around $b=0$ and $c=0$. We will need: $$ \frac{\partial^{p+q}}{\partial b^p \partial c^q} (a+b+c)^{\alpha} = \prod_{k=0}^{p+q-1} (\alpha -k) \cdot (a+b+c)^{\alpha-p-q} = \binom{\alpha}{p+q} (p+q)! \cdot (a+b+c)^{\alpha-p-q} $$ Thus: $$ (a+b+c)^{\alpha} = \sum_{p=0}^\infty \sum_{q=0}^\infty \binom{\alpha}{p+q} (p+q)! \cdot (a)^{\alpha-p-q} \frac{b^p}{p!} \frac{c^q}{q!} = \sum_{p=0}^\infty \sum_{q=0}^\infty \binom{\alpha}{p, q, \alpha-p-q} a^{\alpha-p-q} b^p c^q $$ As you can see, in the case of $\alpha \in \mathbb{N}$, the series terminates, and the expansion reduces to the tri-nomial expansion.

share|cite|improve this answer
Okay, I see, thank you. – Popopo Sep 15 '12 at 13:56

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.